Authoring for Engagement in Plot-Based Interactive Dramatic Experiences for Learning - Schoenau-Fog, Henrik; Bruni, Luis Emilio; Khalil, Faysal Fuad; Faizi, Jawid (Transactions on Edutainment X, 2013)
When developing interactive storytelling applications, most authors have to choose between providing the interacting subjects with either a pre-determined and plot-based narrative structure or a loose arrangement of events, which maintains the freedom of interactivity while sacrificing the author’s control over communicating a theme. To address this problem, this paper contributes a method for organizing narrative events in a free-roaming virtual environment. The Interactive Dramatic Experience Model (IDEM) retains the freedom of navigation while maintaining the possibility to construct various coherent narratives that enable the theme to be communicated. This may be of particular relevance when using digital, interactive, and representational technologies in the mediation of ethically relevant and socially responsible themes. In order to explore the use of the IDEM, we have developed and evaluated the “First Person Victim” application. This interactive experiential storytelling scenario is intended as a tool for teaching about the negative consequences of war.